FROM MISSIONARY TO RESEARCHER: PROFESSIONAL IDENTIFICATION OF PUBLIC SCHOOL TEACHERS UNDERLYING AUTOBIOGRAPHIES WITHIN A CONTINUING EDUCATION PROGRAM - Bagnara, Laura; Kirchhof Ticks, Luciane (Cadernos do IL, 2016)
This research study focuses on autobiographies produced by teachers in two distinct moments (beginning and end) of a continuous teacher education program (CTEP) developed in a public school of Santa Maria (RS, Brazil) in order to analyze the identification teachers established with their profession. To analyze the process of identification with the profession, we consider two textual categories: Modality and Evaluation (FAIRCLOUGH, 2003: 159), since these give an indication of the participants’ commitment to their texts. The results indicate that most participants recurrently assume, at the beginning of the CTEP, the role of “missionary teacher”. At the end of the reflective process, we identified a realignment of the role of “researcher teacher”. KEYWORDS: identity; autobiographies; continuous teaching education program; critical discourse analysis.